1989
DOI: 10.3354/meps054035
|View full text |Cite
|
Sign up to set email alerts
|

Transport of blue crab larvae by surface currents off Delaware Bay, USA

Abstract: Weekly abundance of larval blue crabs CaUinectes sapidus was determined during late summer (1983 and 1984) at 15 stahons on the inner continental shelf within 50 km of Delaware Bay, USA. Simultaneous measurements of subtidal, surface flow were made at 5 current meter stations within the study area. During both years, larval abundance was greatest during early August when concentrations in excess of 100 zoeae m-3 were commonly observed. By the thud week in September, early zoeal stages had &sappeared from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 10 publications
1
60
0
3
Order By: Relevance
“…For example, Epifanio et al (1989) sampled the spatial distribution of crab zoea at weekly intervals and found that this was insufficient to resolve the details of zoeal transport. Subsequent analyses of wind vector and surface current patterns indicated that the distance a parcel of surface water would have travelled during any week was greater than the radius of the study area.…”
Section: Mismatched Scale In Sampling Strategiesmentioning
confidence: 99%
“…For example, Epifanio et al (1989) sampled the spatial distribution of crab zoea at weekly intervals and found that this was insufficient to resolve the details of zoeal transport. Subsequent analyses of wind vector and surface current patterns indicated that the distance a parcel of surface water would have travelled during any week was greater than the radius of the study area.…”
Section: Mismatched Scale In Sampling Strategiesmentioning
confidence: 99%
“…Recruitment to the juvenile phase, however, requires that later larval stages return to the vicinity of an estuary. Blue crab Callinectes sapidus, discussed by Epifanio et al (1989) and Goodrich et al (1989), is a good example of such a n organism.…”
Section: Introductionmentioning
confidence: 99%
“…Blue crab postlarvae return to an estuarine environment in order to settle into nursery areas. Epifanio et al (1989) have argued that although blue crab larvae are transported southward away from the mouth of the Delaware estuary by a narrow buoyancydriven coastal current, larvae that are dispersed offshore may be carried northward again by the mean wnd-driven flow on the inner continental shelf thus enabling them to be retained in the vicinity of the estuary. Likewise Goodrich et al (1989) have argued that wind-driven surface flows, particularly those related to storm events, are important for transporting blue crab megalopae from the open continental shelf into Chesapeake Bay prior to settlement.…”
Section: Introductionmentioning
confidence: 99%